CARCINOMA ADENOIDEO QUÍSTICO LARÍNGEO. CASO CLÍNICO / LARYNGEAL CYSTIC ADENOID CARCINOMA. CLINICAL CASE - Gámez Pérez, Edelberto; Calderón Montero, Yoandry; Columbié Molina, Ariel Ramón; Jiménez Galainena, Julio (Panorama. Cuba y Salud, 2021)
El Carcinoma Adenoideo Quístico supone aproximadamente el 1% de los tumores malignos de la región de cabeza y cuello. Su importancia radica en su curso implacable con múltiples recurrencias locales y metástasis a distancia tardías que disminuyen drásticamente las tasas de sobrevida a los 10 y 15 años. Solo se han publicado 175 casos de Carcinoma Adenoideo Quístico Laríngeo hasta 2015. Presentamos caso en paciente masculino, de localización subglótica y patrón cribiforme. Abstract Cystic Adenoid Carcinoma accounts for approximately 1% of the malignant tumors of the head and neck region. Its importance lies in its relentless course with multiple local recurrences and delayed distant metastasis that drastically lower the rates of life at 10 and 15 years. Only 175 cases of Laryngeal Cystic Adenoid Carcinoma have been published until 2015. We present a case in male patient, subglottic localization and cribriform pattern.